Multiple sclerosis incidence in Al-Madinah Al-Munawwarah in Saudi Arabia before and after the COVID-19 pandemic: a retrospective cross-sectional study - Jaaoini, Yousra H.; Fallatah, Raghad A.; Alsuhaymi, Rawan S.; Alotaibi, Reema N.; Alkuhayli, Ghadi T.; Badr, Sumayah M.; Mufti, Rania E.; Tajuddin, Ameen (International Journal Of Community Medicine And Public Health, 2024)
Background: Many people have suffered from coronavirus 2019 (COVID-19) which was declared pandemic in 2020. More than a year ago, vaccination against COVID-19 offered hope of controlling this pandemic. Recent studies have reported that COVID-19 vaccine can boost immune responses, However, it triggers several neurological diseases such as multiple sclerosis (MS). However, there is insufficient data on COVID-19 infections as a risk factor for MS. Therefore, in this study our aim is to assess the incidence rate of MS before and after COVID-19 Pandemic and the associated findings that appeared in MS patients. Methods: A retrospective cross-sectional study had been conducted using data of patients admitted with COVID-19 infection at King Fahad hospital, Al-Madinah Al-Munawwarah, Saudi Arabia from 2020 to 2024. The collected data had been analyzed using SPSS version 20 using data from medical reports. Results: The overall number of all MS cases that we have collected were 383, the cases before COVID-19 pandemic were 125 cases while 147 cases were during and after COVID-19 pandemic. The brain and spinal lesions was higher than the cases before COVID-19 also, there was a statistically significant difference between the cases that had ataxia before MS before COVID-19 are lower than after COVID- with statistically significant difference. Conclusions: The incident of cases increased after COVID-19, the mean age before COVID-19 was higher than the mean age of cases after COVID-19 with statistical significance difference.